The Ideology of Consumption in Fashion: a Diachronic Per - Gama, Maria (2013)
This article aims to explore the ideology of consumption (in particular, the fashion consumption) diachronically. It begins by reflecting on the genesis and development of a new consumption paradigm in its interdependence with the urban infrastructure, addressing one of its key milestones: the architectural changes operated in Paris in the nineteenth century, at the hands of Haussmann, and the emergence of the department stores. This reflection then focuses on another key aspect: the emergence of shopping malls in Europe, which are considered imaginary universes in this article. It also discusses the ideology of consumption, driven by shopping malls, in the light of the changes caused by the acceleration of consumption and the fast-fashion phenomenon. It highlights, in addition, the new order of incorporation of fashion brands in multinational corporations, which changed the market rules on a global scale. Finally, it focuses on the new consumption cathedrals.